Effect of Al2O3 nanoparticles content and compaction temperature on properties of Al–Al2O3 coated Cu nanocomposites. (15th October 2019) - Barakat, W.S.; Wagih, A.; Elkady, Omayma A.; Abu-Oqail, A.; Fathy, A.; EL-Nikhaily, A.
Abstract: This paper presents experimental investigation on the effect of Al2 O3 content and compaction temperature on mechanical and wear properties of Al–Al2 O3 coated Cu nanocomposites. With the aim of improving wettability and dispersion of high weight fraction of Al2 O3 nanoparticles in Al matrix, Al2 O3 nanoparticles were electroless coated by Cu particles. High-energy ball milling followed by hot compaction was applied to manufacture Al–Al2 O3 coated Cu nanocomposites. The results showed that increasing Al2 O3 nanoparticles content up to 10 wt% improved hardness and wear properties of samples compacted at 400 ᵒ C, while by increasing Al2 O3 content to 15 wt%, the properties were negatively affected due to the agglomeration of Al2 O3 nanoparticles and the high reduction of relative density. However, well dispersion of high content of Al2 O3, 15 wt%, was achieved in samples compacted at 700 MPa which improved hardness by 105% compared to pure Al. The hot compaction temperature highly influenced structural, mechanical and wear properties of compacted samples. Increasing compaction temperature, reduced crystallite size (49 nm) and increased the relative density of Al–Al2 O3 coated Cu nanocomposites which improved mechanical and wear properties of the produced samples. Applying electroless deposition of Cu over Al2 O3 nanoparticles followed by high-energy ball milling and hot compaction at 700 MPa is an efficient procedure for production of Al–Al2 O3 coated Cu nanocomposite with relatively high Al2 O3 content.